(untitled) (Plant Tissue Culture and Biotechnology, 2019)
Immature zygotic embryos of Carica papaya L. var. P-7-9 were inoculated on half-strength MS with different concentrations of 2,4-D and picloram alone and their combinations. The highest induction (80%) of somatic embryogenesis was MS supplemented with 2,4-D (7.0 mg/l) followed by 2,4-D (4.0 mg/l) + picloram (1.0 mg/l) but no embryogenesis was observed in auxin-free medium. The addition of osmoticum such as PEG and ABA significantly increased the maturation of somatic embryos. BAP, TDZ and NAA were used for shoot induction. Combination of 2.0 mg/l BAP and 0.5 mg/l NAA was found significantly better for shoot bud proliferation and 70% multiplication. The percentage of germinating embryos was enhanced significantly when the MS fortified with GA3 (0.5 mg/l). However, the high frequency of embryo germination and plantlets formation were obtained with 2,4-D (4.0 mg/l) + picloram (1.0 mg/l). Plant Tissue Cult. & Biotech. 29(1): 25-32, 2019 (June)